‘Bless and do not curse’: Weaponisation of the Spoken Word in African Pentecostal/Charismatic Christianity - Asamoah-Gyadu, J. Kwabena (Studies in world christianity, 2023)
Christianity in Africa has changed in several ways since the rise of the independent church movement early in the twentieth century. Among the changes that have taken place is the way in which Christianity is instrumentalised against the forces of evil that impair human efforts at flourishing. In contemporary Pentecostal/charismatic Christianity with its emphasis on prosperity and well-being, imprecatory prayers and curses have become important in dealing with the shortfalls of this gospel of success and upward mobility. The use of curses, although justified by its exponents by appeal to various scriptures, also resonates with African traditional systems of thought in which sources of evil are cursed in libation prayers to remove them as obstacles to human self-actualisation believed to be promised by God.